Death Penalty for Corruption Convicts - Lahay, Nadela Ramadhanty Caesarani (CV. Rayyan Dwi Bharata, 2024)
Corruption is an extraordinary and very serious crime in Indonesia, because the crime of corruption never seems to have a solution that makes the perpetrators of the crime feel the deterrent effect. The crime of corruption is regulated in Law Number 31 of 1999 and amended by Law of the Republic of Indonesia Number 20 of 2001 concerning amendments to the Eradication of the Crime of Corruption. In handling corruption offences, a philosophical foundation is required that involves critical thinking, logical analysis, rational reasoning, and deep reflection on fundamental questions about the nature of human existence and the universe. The main objective is to achieve a deep and rational understanding of the reasons, values and fundamental principles that apply in the criminal offence of corruption. And also related to the application of the death penalty which is contrary to human rights stated in article 9 of the Human Rights Law, Article 3 of the UDHR where there are rules that impose the death penalty is prohibited to be applied.